PENGARUH UKURAN PERUSAHAAN DAN OPINI AUDITOR TERHADAP AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR (STUDI KASUS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hamidi Hamidi; Elisa Tarihoran (EQUILIBIRIA, 2020)
This study aims to identify the effect of firm size and auditor's opinion on audit delay, the population used are 54 manufacturing companies listed on the Indonesia Stock Exchange in 2012-2016, and 40 companies selected as samples by purposive sampling technique. The data used is secondary data, and data analysis using multiple linear regression test that is processed by using SPSS Vers. 20. The result of hypothesis testing in this study shows that the dependent variable is audit delay which can be explained by independent variable (firm size and auditor opinion) is 52,6%, this is seen from R Square based on Determination test. The conclusion of this study is firm size partially significant effect on audit delay, and opinion auditor partially significant effect on audit delay at manufacturing company. And simultaneously firm size and auditor opinion have a significant effect on audit delay